2014
DOI: 10.1186/1756-0500-7-128
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum cytokines in response to musculoskeletal surgical trauma

Abstract: BackgroundTrauma induces local and subsequent systemic inflammatory reactions, and when the cytokine production is deregulated, a systemic inflammatory response syndrome with a potentially lethal outcome can occur. The understanding of the physiological mechanism of the cytokine network would be useful to better comprehend pathological conditions.MethodsWe analysed a panel of 30 cytokines in the serum of 20 patients operated with total hip replacement. Cytokine release was assessed postoperatively up to 6 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 31 publications
7
40
1
1
Order By: Relevance
“…However, the sample size restricted to interpret of the obtained data in the present study. Slight increased levels of pro-inflammatory cytokines IL-1, IL-6 due to their stimulator effects on TNF-α production raised the level significantly, meanwhile slight elevation on the level of anti-inflammatory cytokine IL-10 might explain as a consequence of the thyroidectomy operation in accordance with previous studies [19,21] .…”
Section: Kandir Keski̇nsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the sample size restricted to interpret of the obtained data in the present study. Slight increased levels of pro-inflammatory cytokines IL-1, IL-6 due to their stimulator effects on TNF-α production raised the level significantly, meanwhile slight elevation on the level of anti-inflammatory cytokine IL-10 might explain as a consequence of the thyroidectomy operation in accordance with previous studies [19,21] .…”
Section: Kandir Keski̇nsupporting
confidence: 78%
“…Especially IL-1β and TNF-α, IL-6 and C-reactive protein, which is a predictor for acute-phase response and IL-10 have been used in biomarkers for monitoring traumatic inflammation and recovery period in clinically both human and veterinary medicine [18][19][20] . Ozcinar et al [21] reported the pro-inflammatory cytokines IL-1β and TNF-α levels were higher after thyroid surgery in human.…”
Section: Kandir Keski̇nmentioning
confidence: 99%
“…12,37 Previous studies demonstrated the induction of local and systemic inflammatory reactions with production of IL-6 as early as 6 hours after musculoskeletal surgical trauma. 38 In addition, IL-6 shows a distinctive circadian biphasic variation, with concentrations peaking at 4:00 pm and 4:00 am.…”
Section: Discussionmentioning
confidence: 99%
“…B cell differentiation occurs in two phases: the antibodyindependent and antibody-dependent phases. Reikeras et al showed that serum IL-6 significantly increases between 1 and 3 days after hip replacement surgery, 17 and Soto et al reported that serum IL-6 increases significantly after 1 week following aortic valve replacement. These then become antibody-dependent in peripheral lymphatic tissues, and differentiate into antibody-producing plasma cells through na€ ıve B cells, memory B cells and plasmablasts.…”
Section: Discussionmentioning
confidence: 99%